Convents in the system of "balance of powers" in the Frankish kingdom (Teilreich) of the Merovingians - N.Yu. Bikeeva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The relationship between the royal power and the church in the Frankish kingdom of the 6th century has been discussed. Special attention has been paid to the role played by convents in these interactions. The Frankish kingdom, or Teilreich, was a state formation, in which the church was endowed with the functions of secular power, and secular rulers sought to acquire the attributes of religious authority. Under the conditions of political instability, weak bureaucratization, and the broadest system of personal ties, women, including nuns, also appeared in social and political life. Therefore, the author concludes that monasteries, including convents, in the Frankish kingdom of the second half of the 6th century were not only the places of prayer and ascetic way of life, but, at the same time, the “places of power”. During the early Middle Ages, monasteries became important elements in the system of different socio-cultural and political interactions. Because of this, despite their isolation, convents became crucial in the life of urban settlements in this era, fulfilling not only spiritual, but also social, economic and political functions. Their spread in the Frankish kingdom contributed to the establishment of new social contacts and influenced the ways in which the power was realized.